A Culturally Responsive Existential‐Phenomenological Approach for Counseling Black Sexual Minority Youth. Issue 2 (4th July 2020) - White, Dwayne; Palacios, Alfredo
Abstract : This article provides evidence to support developing interventions for addressing the mental health concerns of Black sexual minority youth. The authors identify how to incorporate a culturally responsive existential‐phenomenological approach with storytelling to facilitate the development of a healthy self‐concept among a host of socially enforced categories. Implications are provided to supplement counselors' conceptualization of this population within therapeutic relationships.